2020
DOI: 10.1021/acs.jnatprod.9b01068
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Configuration Assignment to Chiral Natural Products by Biphenyl Chiroptical Probes: The Case of the Phytotoxins Colletochlorin A and Agropyrenol

Abstract: The application of flexible biphenyls as chiroptical probes for the absolute configuration assignment to chiral natural products is described. The method is straightforward and reliable and can be applied to conformationally mobile and ECD silent compounds, not treatable by computational analysis of chiroptical data. By this approach, the (6′ R ) absolute configuration of the phytotoxin colletochlorin A ( 1 ) was confirmed, while the absolute configuration of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 92 publications
1
26
0
Order By: Relevance
“…These are not crystalline compounds; therefore, the use of spectroscopic methods, allowing AC assignment in solution, was required. Moreover, we have recently demonstrated that the NMR-based Mosher approach is sometimes not reliable in the AC assignment to chiral diols, 30 whereas chiroptical methods, that is, ECD, vibrational circular dichroism (VCD), and optical rotatory dispersion (ORD), can provide more general and reliable tools for this task. 31 At first, we attempted to apply for AC assignment to 1 and 2 the use of biphenyl chiroptical probes, 32,33 that we recently demonstrated to be particularly straightforward for naturally occurring diols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are not crystalline compounds; therefore, the use of spectroscopic methods, allowing AC assignment in solution, was required. Moreover, we have recently demonstrated that the NMR-based Mosher approach is sometimes not reliable in the AC assignment to chiral diols, 30 whereas chiroptical methods, that is, ECD, vibrational circular dichroism (VCD), and optical rotatory dispersion (ORD), can provide more general and reliable tools for this task. 31 At first, we attempted to apply for AC assignment to 1 and 2 the use of biphenyl chiroptical probes, 32,33 that we recently demonstrated to be particularly straightforward for naturally occurring diols.…”
Section: Resultsmentioning
confidence: 99%
“…31 At first, we attempted to apply for AC assignment to 1 and 2 the use of biphenyl chiroptical probes, 32,33 that we recently demonstrated to be particularly straightforward for naturally occurring diols. 30 However, compounds 1 and 2 did not allow biphenyl derivatization, as a consequence of their low solubility in the required aprotic solvents. We then decided to employ for the AC assignment to those compounds the ab initio computational analysis of ECD spectra, 34 which proved to be a particularly reliable and straightforward approach for the AC assignment to complex and flexible natural products.…”
Section: Resultsmentioning
confidence: 99%
“…The supramolecular strategy provides an alternative to traditional covalent methods of sensing and detecting analytes associated with inherent chiral or achiral properties [ 18 , 19 , 20 ]. In fact, there are several reports on the use of achiral or dynamically racemic analytes to amplify the chiroptical signal of various cryptochiral molecules, including polymers [ 21 ], oligomers [ 22 ] and macrocycles [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the so-called "chiroptical probes" offer a practical and reliable alternative which is also available to non-specialists in spectroscopy and computations, with the advantage that the configurational assignment can be obtained by a simple visual inspection of the spectrum. Some years ago, we introduced flexible 2,2′bridged biphenyls as chiroptical probes for absolute configuration assignment to chiral diols [17,18], carboxylic acids [19,20] and primary amines [21], eventually extending the chiral detection from ECD to OR measurements [20]. In these systems, thanks to the low aryl-aryl rotational barrier displayed by the biphenyl moiety [17,19], a central-to-axial chirality induction occurs between the chiral substrate and the biphenyl itself which, in turn, assumes a preferred M or P twist depending on the substrate's absolute configuration.…”
Section: Introductionmentioning
confidence: 99%